2006
DOI: 10.1029/2005pa001136
|View full text |Cite
|
Sign up to set email alerts
|

Barium in sediments off northwest Africa: A tracer for paleoproductivity or meltwater events?

Abstract: [1] High-resolution down-core analyses of the solid phase content of total barium (Ba tot ) and total organic carbon (TOC) back to 25 kyr B.P. were performed on a gravity core from the upper continental slope off Cape Yubi (Morocco). The observed discrepancy between the two potential paleoproductivity proxies, Ba tot and TOC, initiated supplementary examinations of the pore water, the geochemistry of the clay fraction, X-ray diffraction analyses, and the application of a sequential Ba extraction method of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 85 publications
(117 reference statements)
1
26
0
Order By: Relevance
“…This finding is in accordance with the results of a study based on a sediment core retrieved nearshore off Cape Yubi (Plewa et al, 2006) showing that Ba is mainly associated with the clay fraction in this region. The results demonstrate that in the study area Ba -except for a few sites off Cape Ghir (c.f.…”
Section: Bariumsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in accordance with the results of a study based on a sediment core retrieved nearshore off Cape Yubi (Plewa et al, 2006) showing that Ba is mainly associated with the clay fraction in this region. The results demonstrate that in the study area Ba -except for a few sites off Cape Ghir (c.f.…”
Section: Bariumsupporting
confidence: 82%
“…Based on these findings we suggest that the suitability of Ba, respectively Ba/Al, as a productivity proxy is limited in this region. We assume that this limitation is mainly based on two different facts: (1) barium is mainly discharged by terrigenous material in this region as discussed in detail by e.g., (Plewa et al, 2006); and/or (2) barite precipitation in the water column is strongly influenced by the variable water depths of the studied sediments (e.g., Von Breymann et al, 1992; Klump et al, 2000).…”
Section: Bariummentioning
confidence: 99%
“…On the contrary, the maxima in Ba bio only occur during the early Holocene, likewise during preceding peak interglacials, when chlorins and biogenic opal already had decreased. Thus the maxima are coeval with pronounced minima in planktic productivity (and in relative nutrient utilization; Galbraith et al [2008]), and on the other hand with prominent preservation spikes of CaCO 3 , for reasons not properly understood, but in harmony with caveats discussed by Plewa et al [2006]. In contrast to Site 882, a Holocene maximum of biogenic Ba in the Bering Sea (Core JPC 17; Brunelle et al [2007]) slightly precedes that of biogenic opal, but clearly lags behind a deglacial CaCO 3 maximum near 15 cal.…”
Section: Standard Series Of Productivity Events Over Termination Imentioning
confidence: 99%
“…[30] Biogenic Ba (Ba bio ) forms a further much cited, although still controversial sediment proxy of paleoproductivity [De La Rocha, 2007;Plewa et al, 2006]. Jaccard et al [2005] established an XRF-based Ba bio record for neighbor ODP Site 882.…”
Section: Biogenic Opal As Paleoproductivity Proxymentioning
confidence: 99%
“…Several recent studies have demonstrated that Ba/Ca shell in foraminifera from marine environments proximal to riverine outflow can be used as an independent proxy for reconstructing paleosalinity (Hall and Chan, 2004;Plewa et al, 2006;Sprovieri et al, 2008;Weldeab et al, 2007). The relationship between riverine Ba/Ca and salinity varies geographically.…”
Section: Planktic Foraminifer Ecology and Geochemistrymentioning
confidence: 99%